Relation between physical exertion and heart rate variability characteristics in professional cyclists during the Tour of Spain - Earnest, C. P.; Jurca, R.; Church, T. S.; Chicharro, J. L.; Hoyos, J.; Lucia, A. (British Journal of Sports Medicine, 2004)
Background: Continued exposure to prolonged periods of intense exercise may unfavourably alter neuroendocrine, neuromuscular, and cardiovascular function. Objective: To examine the relation between quantifiable levels of exertion (TRIMPS) and resting heart rate (HR) and resting supine heart rate variability (HRV) in professional cyclists during a three week stage race. Method: Eight professional male cyclists (mean (SEM) age 27 (1) years, body mass 65.5 (2.3) kg, and maximum rate of oxygen consumption (V·O2MAX) 75.6 (2.2) ml/kg/min) riding in the 2001 Vuelta a España were examined for resting HR and HRV on the mornings of day 0 (baseline), day 10 (first rest day), and day 17 (second rest day). The rest days followed stages 1-9 and 10-15 respectively. HR was recorded during each race stage, and total HR time was categorised into a modified, three phase TRIMPS schema. These phases were based on standardised physiological laboratory values obtained during previous V·O2MAX testing, where HR time in each phase (phase I = light intensity and less than ventilatory threshold (VT; 70% V·O2MAX); phase II = moderate intensity between VT and respiratory compensation point (RCP; 90% V·O2MAX); phase III = high intensity (>RCP)) was multiplied by exertional factors of 1, 2, and 3 respectively. Results: Multivariate analysis of variance showed that total TRIMPS for race stages 1-9 (2466 (90)) were greater than for stages 10-15 (2055 (65)) (p<0.0002). However, TRIMPS/day were less for stages 1-9 (274 (10)) than for stages 10-15 (343 (11)) (p<0.01). Despite a trend to decline, no difference in supine resting HR was found between day 0 (53.2 (1.8) beats/min), day 10 (49.0 (2.8) beats/min), and day 17 (48.0 (2.6) beats/min) (p = 0.21). Whereas no significant group mean changes in HR or HRV indices were noted during the course of the race, significant inverse Pearson product-moment correlations were observed between all HRV indices relative to total TRIMPS and TRIMPS/day accumulated in race stages 10-15. Total TRIMPS correlated with square root of mean squared differences of successive RR intervals (r = -0.93; p<0.001), standard deviation of the RR intervals (r = -0.94; p<0.001), log normalised total power (r = -0.97; p<0.001), log normalised low frequency power (r = -0.79; p<0.02), and log normalised high frequency power (r = -0.94; p<0.001). Conclusion: HRV may be strongly affected by chronic exposure to heavy exertion. Training volume and intensity are necessary to delineate the degree of these alterations.